Heterogeneity based Mode Choice Behaviour for Introduction of Sustainable Intermediate Public Transport (IPT) Modes - Saurabh Kumar; Sanjeev Sinha (Civil Engineering Journal, 2022)
Intermediate public transport (IPT) supplements the public transport system by providing first and last-mile connectivity to commuters. A feeder service based on sustainable intermediate public transportation can be made attractive by improving its mobility, accessibility, convenience, and comfort for its users. Sustainable IPT modes have a lower impact on the environment and can cater to the current and future needs of transportation. In this study, commuters' choice responses were collected using a stated preference survey instrument, and the database was analyzed using a Random Parameter Logit (RPL) model. Face-to-face interviews were conducted with respondents who were approached at random. A different combination of values from the levels of attributes was used to create choice scenarios for each IPT mode. Different types of IPT modes were identified in the study act as feeder services, which was used to find their utility functions using a random parameter logit model. The random parameter logit model with heterogeneity was used to evaluate the impacts of different socioeconomic and trip features on mean estimations. The utility function was used to find willingness to pay (WTP) for different attributes of an IPT mode to assess the relative value of these attributes. It was observed that WTP values also varied between different levels, which were based on their "monthly income level", "trip purpose", and "fare". "High income level" commuters have a higher WTP for travel time, frequency, and comfort improvements. On the other hand, the "work trip" and "high travel fare" levels of commuters have higher WTP for travel time, frequency, and safety improvements. According to the findings of the study, sustainable IPT modes with high quality of service are recommended because of commuters' willingness to pay for improved safety and comfort. The results so obtained can also be used for a better understanding of the travel behaviour analysis of various IPT modes. Doi: 10.28991/CEJ-2022-08-03-09 Full Text: PDF